2022
DOI: 10.1017/s0954579422001055
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–prenatal stress and depression predict infant temperament during the COVID-19 pandemic

Abstract: Researchers have begun to examine the psychological toll of the ongoing global COVID-19 pandemic. Data are now emerging indicating that there may be long-term adverse effects of the pandemic on new mothers and on children born during this period. In a longitudinal study of maternal mental health and child emotional development during the pandemic, we conducted online assessments of a cohort of women at two time points: when they were pregnant at the beginning of the surge of the pandemic in the United States (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Consistent with this hypothesis, prenatal infection stress was positively associated with infant negative emotionality controlling for perinatal depression and anxiety symptoms. These findings align with two previous studies, which found pandemic‐related stress during pregnancy predicted greater negative affect during late infancy (Buthmann et al., 2022; Schweizer et al., 2023). The current study adds to the extant literature by demonstrating these associations during early infancy, which could aid in identifying infants at a younger age who may be at risk for problematic behavioral/emotional outcomes, such as later internalizing and externalizing problems (Gartstein et al., 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with this hypothesis, prenatal infection stress was positively associated with infant negative emotionality controlling for perinatal depression and anxiety symptoms. These findings align with two previous studies, which found pandemic‐related stress during pregnancy predicted greater negative affect during late infancy (Buthmann et al., 2022; Schweizer et al., 2023). The current study adds to the extant literature by demonstrating these associations during early infancy, which could aid in identifying infants at a younger age who may be at risk for problematic behavioral/emotional outcomes, such as later internalizing and externalizing problems (Gartstein et al., 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Among the limited existing studies, researchers in Italy found pandemic‐related stress during pregnancy indirectly predicted poorer infant self‐regulation and positive affect at 3 months through factors such as parenting stress, mother‐infant bonding, and epigenetic changes on stress‐related genes (Provenzi, Grumi et al., 2021; Provenzi, Mambretti et al., 2021). Prenatal pandemic‐related stress has also been demonstrated to continue to predict temperament during late infancy, specifically greater negative affect (Buthmann et al., 2022; Schweizer et al., 2023). In contrast, Sacchi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that prenatal maternal stress has an impact on children’s well-being several years later in life, particularly under stressful circumstances such as the COVID-19 pandemic (H3a). Recent studies have examined the association between prenatal stress and children’s mental health but starting assessment in the pregnancy during the pandemic (Buthmann et al, 2022; Duguay et al, 2022; Provenzi et al, 2021), therefore examining children much younger than the ones investigated in the present sample of 7-10 years old children. In order to examine how children’s development and mental health are affected by prenatal maternal health later in life, subsequent study waves should investigate this association in the present sample at a later stages.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from pregnant cohorts around the world suggests that women experienced elevated symptoms of stress, anxiety and depression during the COVID-19 pandemic [5][6][7][8]. Furthermore, early reports indicate that antenatal exposure to maternal pandemic-related stress (PRS) is associated with early infants' developmental outcomes, including temperament [9][10][11][12], socio-emotional development [13], motor outcomes [14] and even brain connectivity patterns [15].…”
Section: Introductionmentioning
confidence: 99%